Non-Visual Aesthetics: Seeing the World with Our Bodies. Issue 2 (4th May 2018) - Schrag, Anthony
Abstract : This article explores the role of 'physical ontologies' within socially engaged art practices, and explores how the notion of visual art can be limiting for artworks developed with communities and 'non-artists'. It uses the field of embodied cognition and the concept of an anthropology of the body to frame how physical activities can be positioned not only as 'art' but as processes by which artists can ethically explore the world with communities. It therefore provides a counter-narrative to assumptions of how art should function within socially engaged contexts, and examines how physical ontologies become effective – and affective – tools when working in a genre of art that is fundamentally based on humans exchanging with each other in a process of meaning-making. While there are many current discussions about the role of art within the public realm, the formulation of a physical ontology within socially engaged practices has been less explored, and this article provides a reflective discussion point. It is written from the perspective of a practice-based researcher who has worked within the field of participatory/public art for over fourteen years, and provides an example of a physical methodology to frame the argument. This information would be important and interesting for any fields or practitioners working in an engaged or participatory manner with an artist, such as social work, participatory democracy/activisms, or other socially engaged practices.